SINTESIS SILIKA GEL DARI LIMBAH SEKAM PADI (Oryza Sativa) DENGAN VARIASI KONSENTRASI JENIS ASAM - Nur Ainina Nurdin; Takdir Syarif; Nurjannah Nurjannah (Journal of Scientech Research and Development, 2023)
Rice Husk Ash (RHA) is a material that has the potential to be used in Indonesia because of its high production with sampling results during the rice milling process which produces quite a lot of waste, which is equal to 20% of the grain weight with the characteristics of rice husk which is coarse, has low nutritional value, has a high density. low and high ash content. The high content of silica in rice husk can be a reference for its use as a raw material for making silica. Through this research the authors did this to determine variations in the concentration of acid types on the quality of the water content (%) of the resulting silica gel and to determine the characteristics of acid type silica gel. After conducting research using quantitative methods through data collection and data processing, it was found that the concentration of various types of hydrochloric acid (HCl) had a higher level of water content than the type of citric acid (C6H8O7), obtained the concentration of 9 M, while the FTIR test results showed that silica in the type of acid used contained OH groups which identified silanol (SI-OH) absorption range 3450 - 3550 cm-1 and siloxane functional groups (Si-O) absorption ranges of Si-O functional groups, namely 1075 - 1095 cm-1.